The Morphological Deformations and Discrepancy in Sex Ratio in Goldfish (Carassius Auratus) As Biomarker for Pollution in Al- Hammar Marshes – South Iraq - Hassan, Huda (University of Thi-Qar Journal of Science, 2015)
The present study include determine the morphological anomalies and sex ratio disruption for gold fish Carassiusauratus that captured from Al-Hammar marshes during study period that prolonged from October 2013 to May 2014 . the number of captured fish were 106. Morphological anomalies were represent ell by deformity of vertebral column (curved and fusion of vertebrae ) ,face and upper jaws , fin erosion , popeye and eye bleeding . Sex ratio tend strongly towed females (1;25.5).